Copies of «Descriptions of Siberia» by Nicephorus Venyukov in Russian and European libraries XVII – mid XX century: on the history the book monument - T. N. Iljushechkina (Библиосфера, 2014)
The questions of existing the copies of «Descriptions of Siberia» in private and state book collections in Swe- den (the library of Royalgymnasium, Vesteros), Brandenburg (Berlin state library), Poland (the library Yagel- lonskij university, Krakow), Russia (the collection of the manuscripts in Rumyancevskij museum, now – in the State Library of Russia, Moscow; the collection of the manuscripts of earl F. A. Tolstoj and Imperial society of the ancient writing amateurs, Imperial public library, now – in the Russian national library, St. Petersburg).